2019
DOI: 10.1039/c8cs00337h
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-metal metal–organic frameworks

Abstract: Mixed-metal MOFs contain at least 2 different metal ions presenting promising potential in heterogeneous catalysis, gas sorption/separation, luminescence and sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
322
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 545 publications
(332 citation statements)
references
References 151 publications
1
322
0
Order By: Relevance
“…To analyse the possible enhancement of photoluminescence via energy transfer among different lanthanide ions, [39] the mixedlanthanide MUV-5a(Yb0.76Er0.24) was synthesized and characterized (see Supporting Information). The excitation spectra of MUV-5a(Yb0.76Er0.24), MUV-5a(Er) and MUV-5a(Gd) compounds recorded at 295 K and 12 K ( Figure 5) display a broad band from 250 to ca.…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%
“…To analyse the possible enhancement of photoluminescence via energy transfer among different lanthanide ions, [39] the mixedlanthanide MUV-5a(Yb0.76Er0.24) was synthesized and characterized (see Supporting Information). The excitation spectra of MUV-5a(Yb0.76Er0.24), MUV-5a(Er) and MUV-5a(Gd) compounds recorded at 295 K and 12 K ( Figure 5) display a broad band from 250 to ca.…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%
“…1-3, 13, 18-21 Furthermore, by considering their diversity in chemical compositions and structural topologies, MOFs are considered as highly promising candidates for multifunctional materials for their potential application in gas absorption and separation, ionic exchange and identification, conductive and catalytic, magnetic and even ferroelectric properties. 4,22 In particular, some MOFs with perovskite topology showing the coexistence of ferroelectric and magnetic orders, such as AM II (HCOO)3 (A = NH2(CH3)2 (DMA) or NH4; M = Mg, Zn, Mn, Ni, Co, or Fe), 5-7, 18-21, 23-26 have been theoretically predicted and/or experimentally characterized. In these studies, it has been shown that the magnetic order originates from metal ions and the ferroelectric order from the organic molecules through a quite peculiar hybrid improper inversion symmetry breaking mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) or porous coordination polymers (PCPs), constructed from organic ligands and inorganic building units (metal ions or clusters), are an intriguing class of coordination polymers [1][2][3]. There has been a substantial increase in interest of MOFs owing to their attractive physicochemical characteristics such as high surface area, permanent porosity, abundant active sites, and flexible chemical structure [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%